The Global Implications of Domestic Xenophobia: The Case of Chinese Americans - Wicaksana, Fauzan Akbar (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
This study explores the detrimental effects of xenophobia on diplomacy and international relations, focusing on the U.S.-China relationship and the broader Asia-Pacific region. Xenophobia, the fear or hatred of foreigners, has significantly strained bilateral relations, fostering mistrust and hindering cooperation on crucial issues. It has shaped negative public perceptions of China, leading to a climate of fear and intolerance. Economically, xenophobia can lead to protectionism, trade barriers, and a decline in economic activity. It can also disrupt cultural exchange, undermining efforts to build understanding and trust between different cultures. Xenophobia can escalate regional tensions, erode trust among nations, and weaken regional organizations. To address these challenges, regional leaders must prioritize tolerance, understanding, and collaboration. By combating harmful stereotypes, promoting cultural exchange, and addressing economic concerns, they can mitigate the negative impacts of xenophobia and create a more harmonious and cooperative environment for diplomacy and international relations in the Asia-Pacific region